Impact on urban areas of river flooding associated with extreme precipitation events: a case study of Las Liebres creek in León, Guanajuato - Orozco Medina, Ismael; Diaz Buelvas, Alexander José; López de la Cruz , Jesús; Gutiérrez Pérez , Joanna Alicia (Acta Universitaria, 2025)
Floods are the deadliest natural hazards and cause the most extensive damage each year worldwide. This study focuses on evaluating the impact of riverine floods from the Las Liebres stream using a methodology that combines hydraulic modeling, hydrological modeling, and the projection of extreme precipitation events for different return periods, employing frequency analysis with stationary and non-stationary parameters. The results project maximum precipitation events of up to 110 mm with a return period of 100 years, generating a flow rate of approximately 80 m³/s and flooding 13.2% of the urban area of the basin. These floods affect mobility, critical infrastructure, access to basic services, and emergency response capabilities.